2010
DOI: 10.5009/gnl.2010.4.2.212
|View full text |Cite
|
Sign up to set email alerts
|

Virologic Response at 12 Months of Treatment Predicts Sustained Antiviral Efficacy in Patients with Adefovir-Treated Lamivudine-Resistant Chronic Hepatitis B

Abstract: Background/Aims: The aim of our study was to define the potential role of virologic response at 12 months of treatment (VR12) in predicting subsequent virologic and clinical outcomes in adefovir (ADV)-treated lamivudine-resistant chronic hepatitis B. Methods: Two hundred and four patients with lamivudine-resistant chronic hepatitis B virus (HBV) treated with ADV monotherapy were included. Serum HBV DNA was quantified by real-time polymerase chain reactions. VR12 was defined as a HBV DNA level of less than 4 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
3
1
Order By: Relevance
“…Gender was not reported to seemingly affect the response to adefovir treatment except one study which shows that the virologic response to adefovir was better in female patients (Kin et al, 2011;Jung et al, 2010;Aizawa et al, 2011;Reijnders et al, 2009;Ong et al, 2011;Wang et al, 2011;Buti et al, 2007). There was no effect of gender in response to the adefovir treatment in our study.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Gender was not reported to seemingly affect the response to adefovir treatment except one study which shows that the virologic response to adefovir was better in female patients (Kin et al, 2011;Jung et al, 2010;Aizawa et al, 2011;Reijnders et al, 2009;Ong et al, 2011;Wang et al, 2011;Buti et al, 2007). There was no effect of gender in response to the adefovir treatment in our study.…”
Section: Discussioncontrasting
confidence: 62%
“…It has been observed that the probability of virologic response to adefovir treatment was decreased in HBeAgpositive patients (Jung et al, 2010;Reijnders et al, 2009;Wang et al, 2011;Buti et al, 2007). Furthermore, in our study, virologic response to adefovir treatment was better in patients with HBeAg-negativity than patients with HBeAg positivity.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…So, according to their economic conditions, these patients had only the option of self-paid LAM and insurance-covered ADV for the LAM + ADV combination therapy or a discontinuation of LAM with insurance-paid ADV monotherapy [23,25]. Therefore, after achieving VR, many were willing to discontinue the self-paid LAM.…”
Section: Introductionmentioning
confidence: 99%
“…Genotypic resistance was analyzed in some patients with suspected LMV-R CHB and performed using the restriction fragment mass polymorphism method (Green Cross Reference Lab., Yongin, Korea) as previously described. 11 …”
Section: Methodsmentioning
confidence: 99%